Land-use/land-cover change and forest fragmentation in the Jigme Dorji National Park, Bhutan. (2nd January 2017) - Sharma, Kiran; Robeson, Scott M.; Thapa, Pankaj; Saikia, Anup
Abstract: Monitoring land-cover change and understanding the dynamics of forest cover is critically important for the management of forest ecosystems. This study assesses land cover change (1990–2015) in the Jigme Dorji National Park, one of the largest national parks in Bhutan, using Landsat imageries. Overall changes in forest cover, as well as the fragmentation of dense forests within the park, were analyzed using landscape metrics. The results show that total forest area, dense forest area, and moderately dense forest area decreased while open forest area and shrub area increased. During the 25-year study period, the annual deforestation rate was 821 ha year −1, equivalent to 0.63% year −1 . The total number of patches of all type increased by 176%, from 250, 353 to 691, 811, while the mean patch size of forest patches decreased from 1.7 ha to 0.6 ha. The number of smaller patches (0–100 ha size class) in dense forest increased rapidly, indicating that a more fragmented landscape accrued over time, a trend that does not bode well for the maintenance of biodiversity in the national park.